Pengaruh Aktivitas Shalat Terhadap Kontrol Glikemik Penderita DM Tipe 2 di Wilayah Kerja Dinas Kesehatan Kabupaten Kuningan - Hendriana, Yana; Hermansyah, Heri (Sekolah Tinggi Ilmu Kesehatan Kuningan, 2017)
Type 2 Diabetes mellitus (DM) is a chronic disease of carbohydrate, fat, and protein metabolism disorders, which is characterized by elevated chronic blood glucose (hyperglycemia) levels. The sustainable hyperglycemia is able to cause disruption of the entire system of body. This research aimed at finding out the influence of the five-time prayer implementation on the decrease of fasting blood glucose level of type 2 diabetes mellitus. The study employed a quasi experimental research by one group pre and post test design without control group. The number of samples of 15 respondents was determined by purposive sampling technique. The result of statistical analysis showed that there was the significant influence between the five-time prayer implementation and the decrease of fasting blood glucose, the average decrease was 93,113 and p value=0,000. The decrease in fasting blood glucose after the intervention of prayer activity in the form of the implementation of five-day prayers for 3 days caused by the body's physiological effects enhanced GLUT 4 translocation and increase the psychological effects of mind relaxation that occurred during the five-time prayer practice